Condiciones para iniciar el uso social del cementerio Miraflores de Trujillo como monumento histórico parte del patrimonio cultural nacional - Velasquez Chero, Junior Andres (2020)
ABSTRACT The present investigation was born with the purpose of being the starting point to generate new and better conditions to Miraflores cemetery of Trujillo as historical monument of the nation part of the national cultural heritage. These new conditions are proposed in order to revalue the cultural heritage and start its social use in an appropriate manner. The investigation proposes the beginning of the social use of the Miraflores cemetery of Trujillo through four central axes, the investigation of the historical roots of the real estate, the delimitation of the area that would have the status of historical monument, the analysis of the condition in which it is currently located. and the degree of acceptance that would have generate a new use different from the current Miraflores cemetery. All this to be able to care for and revalue the Miraflores cemetery in Trujillo as a historical monument. We worked based on the historical research of archival sources, observational and photographic recognition, as well as working with surveys to achieve all the proposed objectives. The investigation concluded that, The realization of the Miraflores cemetery recognition of Trujillo determined that the patrimonial pare recognized as a historical monument of the nation should be a third of the total cemetery, duly sustained and subdivided into four zones according to artistic and historical support of each one; the Miraflores cemetery of Trujillo is at risk due to the affectations found, which are anthropic, biological and environmental, a fact that provokes its declaration of at risk; the archival analysis helped to establish the historical, artistic and cultural relevance of the Miraflores cemetery of Trujillo as a historical monument, helping to understand the roots within society; Trujillo's society is receptive to an alternative social cultural use to funerary use; and the work proposal consists of four parts to start the social use of the Miraflores cemetery of Trujillo as a historical monument, these are based on the recognition of the place, the prevention and the level of acceptance of the population.